(untitled) (Applied Biological Research, 2022)
Dye-sensitized solar cells (DSSCs) are promising types of photovoltaic cells which have the capability to generate electrical energy at low fabrication cost in comparison to the silicon crystalline solar cells. Titanium dioxide (TiO2) nanoparticles were synthesized by solvothermal method. DSSCs using Ixora macrothyrsa flowers as dye-sensitizer were fabricated using l as solvents. The structural and surface properties of TiO2 nanoparticles were characterized using X-ray diffraction and Field Emission Scanning Electron Microscopy. The synthesized TiO2 material had tetragonal crystal structure which was highly stable and crystalline. The extracted natural dyes were characterized by UV-visible absorption pectroscopy and Fourier transform infrared (FTIR). The bandgap energy of TiO2 photoanode was studied by using UV-visible spectra and the y using FTIR spectra. The photo-electrochemical parameters and efficiency of DSSC were measured using-measurement system. The result of J-V characteristics showed that the efficiency of DSSC’s based on TiO2 nanoparticles extracted from Ixora flowers using ethanol solvent was better than water solvent.